2019
DOI: 10.1186/s12912-019-0355-x
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological cancer inpatients need more supportive nursing care than outpatients: a comparative study

Abstract: Background Gynecological cancer inpatients and outpatients may have distinct supportive nursing care needs. This study aimed to compare the supportive care needs between these two patient cohorts. Methods This cross-sectional comparison analytic study aimed to identify the differences between the supportive nursing care needs of the gynecological cancer inpatients and outpatients. Data were collected from 200 participants who were recruited through consecutive sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
0
11
0
3
Order By: Relevance
“…Similarly, both inpatients groups of patients and their FCs have more needs as compared to outpatients. Mawardika et al [57] reported that gynaecological cancer patients' physical and psychological supportive care is comparatively higher (44 times) for those receiving inpatient care than those receiving outpatient care. Besides, the financial cost associated with hospitalization is considerably higher than outpatient and as such, they logically have more needs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, both inpatients groups of patients and their FCs have more needs as compared to outpatients. Mawardika et al [57] reported that gynaecological cancer patients' physical and psychological supportive care is comparatively higher (44 times) for those receiving inpatient care than those receiving outpatient care. Besides, the financial cost associated with hospitalization is considerably higher than outpatient and as such, they logically have more needs.…”
Section: Discussionmentioning
confidence: 99%
“…Among others, the advanced stage of cancer is in its turn confirmed to be a predictor of mental distress in women with breast and ovarian cancer [ 40 , 41 ]. Overall, our findings point to the importance of the establishment of a program taking into account and responding to specific psychological needs of patients with breast and gynecological cancer [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 90%
“…Considering the quality of current evidence, we find that Outcome: FACT-F: functional assessment of cancer therapy fatigue; FACT-G: functional assessment of cancer therapy-general; BDI: Beck Depression Inventory; SAI: state anxiety inventory; HADS: hospital anxiety and depression scale; HDRS: Hamilton depression rating scale; ESAS: Edmonton symptom assessment scale; VAS: visual analog scale. 6 Evidence-Based Complementary and Alternative Medicine Evidence-Based Complementary and Alternative Medicine research on art therapy of gynecologic cancer patients is insufficient. We cannot draw the conclusion that art therapy benefits gynecologic cancer patients in the psychological outcome, QOL, and cancer-related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cervical cancer is the fourth most common cancer in women, and the seventh overall, accounting for 7.5% of all female cancer deaths [4]. e patients with gynecological cancer may suffer from psychological distress, fatigue, sleep disturbance, urinary/bowel issues, lymphedema, menopausal symptoms, and sexuality issues [5][6][7]. Side effects of treatment, complications, and cumulative organ toxicities may alter the patient's body function, interfere with daily activities, have a negative impact on QOL [8], as well as distorting their psychological states, body image, body awareness, and selfesteem [2].…”
Section: Introductionmentioning
confidence: 99%